A multidimensional approach to knowledge coproduction in glaciology - Marcela Brugnach; Saria Sato-Bajracharya; Lisa Kranz; Nerea Bilbao-Barrenetxea; Sergio Henrique Faria (Journal of Glaciology)
This work presents a reflection on the meaning and significance of knowledge coproduction in the field of glaciology. We start by invoking the paradigm of Structure–Form–Environment Interplay (SFEI) to formulate a generalised definition of glaciology, which highlights the relevance of knowledge coproduction. The adoption of a relational view of glaciological knowledge leads us to identify five core dimensions of knowledge coproduction: purpose, ethics, ambiguity, inclusion/exclusion, and relationships. Based on those dimensions, we delve into the decisive methodological aspects of the coproduction process, namely the definition of its purpose, the identification of participants, the organisation of the process, the recognition of ambiguity in Ways of Knowing (WoKs), and the consideration of ethical implications. In addition to the already known three stages of knowledge coproduction process (codesign, codevelopment, and codelivery), we propose the inclusion of an additional preparation stage, which entails the acknowledgment of the identity and involvement of all human and nonhuman participants, their positionality, and means to ensure their cultural and ontological safety. We reason that knowledge coproduction does not replace the scientific method, but rather complements it, eliciting the possibility to unveil deeper insights that might be difficult to attain through unilateral means.